To solve the system of equations given by:
\[ \begin{cases} 8x - 4y = 16 \quad \text{(1)} \ 8x + 4y = 16 \quad \text{(2)} \end{cases} \]
let's first manipulate these equations.
-
From equation (1): \[ 8x - 4y = 16 \] We can solve for \(y\): \[ -4y = 16 - 8x \] \[ 4y = 8x - 16 \] \[ y = 2x - 4 \quad \text{(3)} \]
-
From equation (2): \[ 8x + 4y = 16 \] Similarly, we can solve for \(y\): \[ 4y = 16 - 8x \] \[ y = 4 - 2x \quad \text{(4)} \]
Now we have two expressions for \(y\) from equations (3) and (4): \[ y = 2x - 4 \quad \text{(3)} \] \[ y = 4 - 2x \quad \text{(4)} \]
Setting these two expressions for \(y\) equal to each other: \[ 2x - 4 = 4 - 2x \] Now, solve for \(x\): \[ 2x + 2x = 4 + 4 \] \[ 4x = 8 \] \[ x = 2 \]
Now substituting \(x = 2\) into either equation (3) or (4) to find \(y\). Let's use equation (3): \[ y = 2(2) - 4 \] \[ y = 4 - 4 \] \[ y = 0 \]
So, the solution to the system of equations is: \[ x = 2, \quad y = 0 \]
Final answer: \[ x = 2 \] \[ y = 0 \]